Information, Truth and Post-truth: a pragmaticist critique on Information Science - Bocardi de Moraes, Sonia Cristina [UNESP]; Almeida, Carlos Candido de [UNESP]; Lima Alves, Marcus Rei de [UNESP] (Univ Federal Santa Catarina, 2020)
Objective: The article seeks to highlight the truth criteria contained in the informational processes, both the scientific ones that circulate in the representations of the facts in the society, and to maintain Information Science (IS), as a provider of the true proof of reality. Given the dissemination of content in networks that are part of the Internet and are called information without the correct correlation with the facts, it is necessary to list elements within the scientific field to understand these contents, which tend to be accepted as true without this proof. Methods: The action of the users in the computer network reported as information, as well as the approach in the IS of the diffusion of knowledge within the society, has in the bibliographical revision the revision of the foundation of the Peircean Pragmatism for use of the Pragmatic Method as a possibility of instrument of the IS. Results: The disclosure of true scientific knowledge is the paradigm contained in the IS, which must be extended to the informational relations disclosed to society. The concept of information implies in the ways of communication. This interrelationship of information and its epistemological character are implicit in the process of signification. The interrelation between message and information is a fundamental part of true semiosis. The production of inference that produces knowledge for the subject, mediated by the sign, implies in information. Conclusions: It is up to the IS to promote the scientific method of fixing the truth, and here the Pragmatist proposal is considered as that which deals with both the scientific truth and the truth of the facts.
Keywords: Information; Peircean Pragmatism; Truth; Information Science; Semiosis